Susceptibility of Clostridium perfringens Isolated from Human Infections to Twenty Antibiotics - Schwartzman, Joseph D. (1977)
The proper choice of antibiotic for Clostridium perfringens infections in patients allergic to penicillin is not clear; the usual recommendations and recent in vitro studies disagree. We tested the susceptibility of 57 strains of C. perfringens to eight penicillins, seven cephalosporins, two tetracyclines, clindamycin, chloramphenicol, and rifampin by the agar dilution method. All strains were inhibited by (per milliliter) 4 μg or less of any of the penicillins, chloramphenicol, or clindamycin and 8 μg or less of any of the cephalosporins tested. Penicillin G and amoxicillin inhibited all strains at 0.12 μg or less per ml. Only 54% of the strains were inhibited by 1 μg of tetracycline per ml. Penicillin G remains the drug of first choice for infections with C. perfringens; it need not be added to a regimen containing a penicillinase-resistant penicillin given parenterally in high doses. The cephalosporins should be considered as alternative drugs for penicillin-allergic patients. Clindamycin and chloramphenicol are also effective. Tetracyclines cannot be depended upon in clostridial infections without in vitro testing, which is impracticable for initial empirical therapy.